IMPLEMENTASI PERATURAN DAERAH NOMOR 2 TAHUN 2016 TENTANG PENYELENGGARAAN PERLINDUNGAN ANAK DI KOTA BATAM - Debora, Debora Tamba; Epriadi, Dedi (LPPM Universitas Putera Batam, 2022)
The Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection isconsidered to ensure protection from discrimination, violence, and other violations. The purpose of thisstudy is to describe the implementation of Regional Regulation Number 2 of 2016 concerning theImplementation of Child Protection in the city of Batam, to analyze the inhibiting factors in theimplementation of Regional Regulation Number 2 of 2016 concerning the Implementation of ChildProtection in the city of Batam. The type of research method used is descriptive qualitative methodwith interview, observation, and documentation data collection techniques. The data sources of thisresearch consist of primary data and secondary data. The results of the study show thatcommunication, namely 1.Communication of the Office of Social Affairs and CommunityEmpowerment has communicated quite well by involving community leaders, social services, socialservice assistants then the police, perpetrators, and victims and the community is aware of the servicethat protects children. According to the researcher, the communication between the Social Service andcommunity empowerment should be further improved so that the community and victims dare to reportto the Social Service and community empowerment. Regarding adequate facilities for child protectionprograms, only additional people are needed for social workers in the child protection division, 3.Disposition, namely the authority Keywords: Implementation, Child, Batam